The traditional maximal lactate steady state test versus the 5× 2000 m test - Legaz Arrese, Alejandro; Carranza García, Luis Enrique; Serrano Ostáriz, Enrique; González Ravé, J. M.; Terrados, Nicolás (Georg Thieme Verlag KG, 2011)
Here, we compared the maximal lactate steady state velocity (vMLSS) estimated from a single-visit protocol (v5 × 2000) to the traditional multi-day protocol (vMLSS). Furthermore, we determined whether there was a lactate steady state during the time limits (Tlim) at vMLSS or v5 × 2000. Eight runners completed a half marathon (HM), the traditional protocol to determine the vMLSS and the 5 × 2000 m test in a randomised order, and a Tlim at vMLSS and at v5 × 2000 in a randomised order. The vMLSS (13.56 ± 0.90 km·h − 1 ) was higher than the v5 × 2000 (12.93 ± 0.90 km·h − 1 , p = 0.001) and comparable to the vHM (13.34 ± 0.75 km·h − 1 ). The vMLSS (r = 0.83) and the v5 × 2000 (r = 0.91) were associated with the vHM but were not indicative of the competition pace. The Tlim at vMLSS (64 ± 15 min) was lower than the Tlim at v5 × 2000 (94 ± 21 min) and the HM time (95 ± 5 min). In both Tlim, lactate was lower at 45 min than upon fi nishing the eff ort and was predictive of its duration (p < 0.05). Our results indicate that the 5 × 2000 m test can be equally useful to assess runners as the traditional MLSS protocol and that there is no lactate steady state during the Tlim at vMLSS or at v5 × 2000